Chapter 1: Introduction: A Research Agenda for Human Rights and the Environment - Lupin, Dina (Edward Elgar Publishing, 2023)
This chapter introduces the volume, pulling together key themes and idea and summarizing the chapters. It sets out the agenda of the book which is to call for resistant, transformative and inclusive research and practice in the area of human rights and the environment, that centres the knowledges, practices, laws and priorities of marginalised groups by putting human rights law and tools to the greatest possible work to address environmental injustice.